2014
DOI: 10.1089/acm.2013.0364
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Acupuncture Use in the Treatment of Cognitive Impairment After Stroke

Abstract: Objective: This meta-analysis was conducted to evaluate the efficacy of acupuncture on cognitive impairment (function) after a stroke. Design: Randomized controlled trials (RCTs) comparing acupuncture with no acupuncture in addition to medicine or rehabilitation were identified from databases (PubMed, Cochrane Central Register of Controlled Trials, Chinese National Knowledge Infrastructure, VIP Chinese Periodical Database, Wangfang Chinese Periodical Database, Chinese Bio-medicine Database, Cochrane Library, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 31 publications
(32 reference statements)
0
78
0
Order By: Relevance
“…Using this test in previous studies (23,24,32), EA was shown to improve the memories of rats following stroke. Previous clinical studies and meta-analyses have demonstrated that EA exerts a positive effect on cognitive function when compared with no acupuncture, medicine or rehabilitation (11,12,33). Furthermore, a series of clinical trials have shown that acupuncture regulates the release of neurochemicals, hemorheology, cerebral microcirculation, metabolism, neuronal activity, and the function of specific brain regions (10,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Using this test in previous studies (23,24,32), EA was shown to improve the memories of rats following stroke. Previous clinical studies and meta-analyses have demonstrated that EA exerts a positive effect on cognitive function when compared with no acupuncture, medicine or rehabilitation (11,12,33). Furthermore, a series of clinical trials have shown that acupuncture regulates the release of neurochemicals, hemorheology, cerebral microcirculation, metabolism, neuronal activity, and the function of specific brain regions (10,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture (EA), a non-drug therapy based on Traditional Chinese Medicine, may have a role in promoting recovery of neurological function. 3 A meta-analysis has suggested that acupuncture has positive effects on PSCI 4 and our previous clinical study showed that EA at GV20 (Baihui) and GV24 (Shenteng) improved cognitive function and contributed to the comprehensive rehabilitation of stroke patients. 5 6 Cerebrovascular diseases can cause irreversible neurodegeneration, leading to global cognitive impairment and progressive dementia.…”
Section: Introductionmentioning
confidence: 98%
“…Approximately 64% of stroke patients are often followed with cognitive impairment and 33% of them turn into dementia existing for several months during decubation [2]. Cognitive deficits arise frequently after ischemic stroke, which cause difficulties with analysis, concentration, organization, interpretation, and other abates in cognitive functions that bring about the low quality of life [3, 4]. The dysfunction of learning and memory is the cardinal symptom of cognitive impairment after stroke and is the main culprit of persistent sequelae [5].…”
Section: Introductionmentioning
confidence: 99%